Pengaruh Pemeliharaan Kesehatan Mulut Ibu Hamil terhadap Status Tumbuh Kembang Janin: The Effect of Maternal Oral Health Maintenance on the Status of Fetal Growth and Development - Vina, Vina Dwi Wahyunita; Hermanses , Sitti S. (Jurnal Bidan Cerdas, 2021)
Introduction: At Lorulun Public health Center, pregnant women who do Antenatal Care (ANC) visits with complaints around the mouth are still quite high (89.8%), and the implementation of health promotion for maintaining oral health during pregnancy is rarely carried out in a structured manner in conjunction with other pregnancy counseling activities. The aim to determine the effect of oral health maintenance in pregnant women on the growth and development of the fetus during pregnancy. Methods: This study is a quasi-experimental design with a non-equivalent control group design of two groups with a total sample of 64 respondents. Sampling was done using a purposive method. Data analysis of growth and development variable was carried out using independent t-test, oral hygiene variable was analyzed using Mann Whitney test and oral hygiene was analyzed using ANOVA test. Results: The results of this study showed that health education methods (video and demonstrations) were effective in increasing the average growth status of the fetus with TFU 28.06 (cm) TBJ 2334.69 grams and reducing the OHIS value of 1.26 (better oral hygiene), while oral hygiene was not affect the status of fetal growth and development. Conclusion: Oral hygiene does not affect the growth and development of the fetus, but it is hoped that pregnant women will continue to pay attention to their oral hygiene during pregnancy because oral hygiene affects the intake of nutritional needs that enter the fetus.